Challenges and Opportunities of Madrasah Graduates in the NewAutonomous Region in the Philippines - Rakim Sammy; Abdul Lantong (Program Studi Manajemen Pendidikan Islam, Fakultas Tarbiyah dan Ilmu Keguruan, IAIN Ponorogo, 2026)
Despite a long history of colonization and marginalization, madrasah education has continued to flourish in the Bangsamoro region. Graduates have been deprived of formal higher education, and the limited job opportunities widened the socio-economic gap and educational inequity. As new autonomy emerges, this study aims to examine the impact of the reform on government policy toward madrasah education, as well as the challenges and opportunities for graduates. The study involves four participants from a traditional madrasah. Investigating their lived experiences through narratives and semi-structured interviews captures their perspectives about previous and current programs. Thematic analysis found that the new government reform positively impacted both the madrasah system and graduates. Madrasah education was systematized through permits to operate and government recognition; graduates were provided opportunities through the ISAL program and career development. It also improves the economic status of madrasah graduates and widens employment opportunities. Although traditional madrasahs face challenges inproviding quality education, obtaining government recognition, government reforms have changed perceptions of their capacity to produce graduates who contribute to society. Therefore, it is necessary to evaluate current program policies governing the recognition of madrasahs to access government funds.